Rare-Earth-Doped Nanoparticles for Short-Wave Infrared Fluorescence Bioimaging and Molecular Targeting of αVβ3-Expressing Tumors. (18th September 2018) - Naczynski, Dominik Jan; Stafford, Jason H.; Türkcan, Silvan; Jenkins, Cesare; Koh, Ai Leen; Sun, Conroy; Xing, Lei
The use of short-wave infrared (SWIR) light for fluorescence bioimaging offers the advantage of reduced photon scattering and improved tissue penetration compared to traditional shorter wavelength imaging approaches. While several nanomaterials have been shown capable of generating SWIR emissions, rare-earth-doped nanoparticles (REs) have emerged as an exceptionally bright and biocompatible class of SWIR emitters. Here, we demonstrate SWIR imaging of REs for several applications, including lymphatic mapping, real-time monitoring of probe biodistribution, and molecular targeting of the αv β3 integrin in a tumor model. We further quantified the resolution and depth penetration limits of SWIR light emitted by REs in a customized imaging unit engineered for SWIR imaging of live small animals. Our results indicate that SWIR light has broad utility for preclinical biomedical imaging and demonstrates the potential for molecular imaging using targeted REs.